O Heitor de Homero e as diversas faces do medo - Fortuna, Gabriel Galdino [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work aims to expose the cultural elements responsible for constructing and defining the figure of the Homeric hero. Therefore, it was selected one of the most important characters in the Iliad, Hector, a warrior who, by acting in various ambits, becomes able to represent as many characters as possible present in the epic. In order that the study reach these goals, we have invested in an analysis to investigate the quoted character based on his first and most sincere reactions, that is, those related to fear. We chose fear because of its constant and detached presence in the bellicose context in which the Iliad is worked, moreover, the interaction this emotion owns with the Homeric hero was able to compile all the motivator elements of Hector and, consequently, works as a resource for understanding of the hero. This catalyst function of values that fear has, emerged through the Aristotelian and Socratic views, that enabled the distinction and understanding of other concepts that are inextricably linked to that emotion, such as courage, confidence, cowardice and alienation. The combination between Hector and fear was a choice that was fundamental to execute the analytical study of the Homeric hero, since there is nothing more coherent to understand the hero than to confront the emotion able to gather as much values as possible with the character, able to act in several different situations, becoming a perfect model that could be used as a reflection of the other heroes of the narrative. The exposition of how fear becomes linked to the hero led to the clarification that this emotion is able to act paradoxically, since as well as it can take the warrior to path of dishonor, without it, there would not be courage in order that glory could be achieved. Toward these questions, we affirm that the following text will work with an ambiguous emotion related to a paradoxical character, after all, the Homeric hero is a mythical and...

Este trabalho tem por objetivo expor os elementos culturais responsáveis por construir e delimitar a figura do herói homérico. Para tanto, selecionou-se uma das personagens mais importantes da Ilíada, Heitor, um guerreiro que por atuar em vários âmbitos torna-se capaz de representar o maior número possível de personagens presentes no épico. Para que este estudo atinja tais objetivos, investiu-se em uma análise que investigasse a personagem citada baseada em suas reações primeiras e mais sinceras, ou seja, àquelas relacionadas ao medo. Optou-se pelo medo devido a sua constante e destacada presença no contexto bélico em que a Ilíada é trabalhada, além disso, a interação que esta emoção possui com o herói homérico foi capaz de compilar todos os elementos motivadores de Heitor e, consequentemente, funcionar como um recurso para a compreensão do herói. Esta função catalisadora de valores que o medo possui surgiu por intermédio da visão aristotélica e socrática que possibilitou a distinção e compreensão dos demais conceitos que são indissociáveis a esta emoção, como a coragem, a confiança, a covardia e a alienação. A combinação entre Heitor e o medo foi uma escolha que provou ser fundamental para executar o estudo analítico do herói homérico, visto que não há nada mais coerente para se compreender o herói do que confrontar a emoção capaz de reunir o maior número de valores possíveis com a personagem capaz de atuar em várias situações distintas, constituindo um perfeito modelo que pudesse ser usado como reflexo dos demais heróis da narrativa. A exposição de como o medo se articula com o herói levou ao esclarecimento de que esta emoção é capaz de atuar paradoxalmente, pois assim como pode levar o guerreiro ao caminho da desonra, sem ela, não existiria coragem para que a glória pudesse ser atingida. Diante destas indagações, afirma-se que o texto a seguir trabalhará com uma...
Keywords: Homero Ilíada; Literatura; Medo; Heróis; Literature